CHANGES IN THE STRUCTURES OF SMALL CITIES – A DOCUMENTATION OF LAND USE PATTERN CHANGES IN SELECTED REGIONS OF THE PROVINCE STYRIA (AUSTRIA) - Sulzer, Wolfgang; Droin, Ariana (Turisztikai és Vidékfejlesztési Tanulmányok, 2021)
The paper deals with the documentation of land use pattern changes in selected small urban regions in the Province Styria (Austria). The first part describes some useful definitions like “land consumption”, “built up area”, and “land cover and land use” in the context of Remote Sensing recording. In the following, different nomenclatures for Urban Remote Sensing Analyses from the Copernicus Land Monitoring Service such as the “CORINE Land Cover”, “Impervious Products”, “European Settlement Map” and the “Urban Atlas” will be documented and compared with the “Land Information System Austria – LISA” and local “Land Use Classification System” for the city of Graz. Several selected case studies/maps of small cities (Fohnsdorf/Judenburg, Liezen, Leibnitz and Deutschlandsberg) in Styria are proofing that a continuously observation of land consumption and land use pattern changes can be guaranteed by the analyses of different remote sensing data sets.